2-Hydroxy- N ′-((Thiophene-2-yl)methylene)benzohydrazide: Ultrasound-Assisted Synthesis and Corrosion Inhibition Study - Singh A.K.; Thakur S.; Pani B.; Ebenso E.E.; Quraishi M.A.; Pandey A.K. (My University, 2025)
2-Hydroxy-N′-((thiophene-2-yl)methylene)benzohydrazide (HTMBH) was synthesized by conventional method as well as by ultrasonication (US). The ultrasound-assisted synthesis of HTMBH was found to have good yield and be more eco-friendly compared to the conventional method of synthesis. The synthesized compound HTMBH was characterized by Fourier transform infrared, 1H NMR, and CHN analyses. The corrosion inhibition behavior of HTMBH was investigated using gravimetric and electrochemical methods in 0.5 M H2SO4. The thermodynamic adsorption parameters revealed that HTMBH was adsorbed on the mild steel surface in both ways, physically and chemically, although physisorption is predominant. The study of activation parameters revealed that it is the increase in activation energy that is a prominent factor to lower the corrosion rate in acid medium. Atomic force microscopy analysis is also carried out to investigate the effect of HTMBH on the surface of mild steel surface in acid solution. The contact angle measurement showed decreased affinity of mild steel surface for acid solution containing HTMBH. The results obtained from all of these methods showed good consistency. © 2018 American Chemical Society.